Răspuns:
1)
M(SO₃) = A(S) + 3A(O) = 32 + 3 × 16 = 80 kg/kmol
n(SO₃) = m(SO₃) / M(SO₃) = 80 kg / 80 kg/kmol = 1 kmol
2SO₂ + O₂ → 2SO₃
2 kmol SO₂.....2 kmol SO₃
x = 1 kmol SO₂.....1 kmol SO₃
M(SO₂) = A(S) + 2A(O) = 32 + 2 × 16 = 64 kg/kmol
m(SO₂) = n(SO₂) × M(SO₂) = 1 kmol × 64 kg/kmol = 64 kg
2)
S + O₂ → SO₂
2SO₂ + O₂ → 2SO₃
SO₃ + H₂O → H₂SO₄
M(H₂SO₄) = 2A(H) + A(S) + 4A(O) = 2 × 1 + 32 + 4 × 16 = 98 kg/kmol
n(H₂SO₄) = m(H₂SO₄) / M(H₂SO₄) = 98 kg / 98 kg/kmol = 1 kmol
n(H₂SO₄) = n(SO₃)
n(SO₃) = n(SO₂)
n(SO₂) = n(S)
→ n(H₂SO₄) = n(S) = 1 kmol
m(S) = n(S) × A(S) = 1 kmol × 32 kg/kmol = 32 kg
-Mihai